(untitled) (Journal of Comparative & International Higher Education, 2022)
Despite the central role played by faculty within Higher Education Institutions (HEIs) in addressing Gender -Based Violence (GBV), their experiences have received limited attention, especially in the context of HEIs within South Asia. The study seeks to fill this research gap by exploring teaching faculty’s (n=10) experiences with addressing GBV in a public HEI in Delhi (India) through the use of narrative inquiry. Narrative inquiry was chosen because it is participant-led, open ended, and collaborative; thereby providing more space for the faculty to share their experiences when dealing with GBV. Analysis of data from a pilot interview conducted with a senior female faculty member revealed that female victims typically refuse to lodge a formal complaint due to the fear of social stigma, and advocacy for victims of GBV by the faculty in the absence of institutional support tends to take a psychological toll on them. In addition, safeguarding the college’s reputation is a key concern for the organization, which often dissuades victims from coming forward. The preliminary findings highlight the need for greater institutional support to enable the faculty to advocate for GBV, as well as the nexus between the gendered social structure and institutional/personal responses to GBV. It also draws attention to the need to include the voices of diverse faculty members who have dealt with cases where boys were victims of GBV as my study goes forward to develop a more holistic understanding of how gendered social structures inflict violence on both women and men.